Availability constraints of plant protection products in Polish winter cereal production – a post-EU accession perspective - Strażyński, Przemysław; Kierzek, Roman; Mrówczyński, Marek (Journal of Plant Protection Research, 2025)
Due to their extensive cultivation and the significant impact of pests causing economically relevant losses, winter cereal crops require effective chemical protection. A major challenge in their protection is the steadily diminishing range of available plant protection products (PPPs), specifically the active substances (AS) they contain. Although the core principles of the European Green Deal have been temporarily suspended, the European Commission has continued to phase out several active substances. As a result, dozens of these substances have been withdrawn from the market in recent years, creating increasing difficulties in crop protection - particularly for winter cereals. This is partly due to the growing resistance of pests, stemming from reduced opportunities for rotating products with different mechanisms of action. Further reductions in active substances, in the absence of viable alternative methods for agrophage control, may potentially lead to a decrease in both the cultivated area and overall production volumes for economic reasons. Moreover, such a scenario increases the risk of illegal imports or off-label use of plant protection products (PPP).